2020
DOI: 10.2147/cmar.s243869
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Long Noncoding RNA <em>LINC00173</em> Promotes the Malignancy of Melanoma by Promoting the Expression of IRS4 Through Competitive Binding to microRNA-493</p>

Abstract: Purpose: Long intergenic non-protein-coding RNA 173 (LINC00173) plays crucial roles in lung cancer. However, the expression and biological functions of LINC00173 in melanoma have not yet been investigated. In this study, we aimed to characterize the involvement of LINC00173 in melanoma and elucidate its mechanisms of action. Materials and Methods: Reverse-transcription quantitative PCR was performed to measure LINC00173 expression in melanoma. A CCK-8 assay, flow cytometry, and migration and invasion assays we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…For example, LINC00173 was found to regulate cervical cancer cell viability and invasiveness via the miR-182-5p/F-box and the WD repeat domain-containing 7 axes (11). Furthermore, lncRNA LINC00173 accelerated breast cancer progression by downregulating miR-490-3p (12), and accelerated the development of melanoma by upregulating insulin receptor substrate 4 via miRNA-493 sponging (13). However, the function of LINC00173 in HCC chemoresistance remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, LINC00173 was found to regulate cervical cancer cell viability and invasiveness via the miR-182-5p/F-box and the WD repeat domain-containing 7 axes (11). Furthermore, lncRNA LINC00173 accelerated breast cancer progression by downregulating miR-490-3p (12), and accelerated the development of melanoma by upregulating insulin receptor substrate 4 via miRNA-493 sponging (13). However, the function of LINC00173 in HCC chemoresistance remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Through the limma analysis, we identified the top 10 DELs. Among them, NCRNA00173 was found to be involved in the progression, of various tumors, such as lung squamous cell carcinoma ( 20 ), prostate cancer ( 21 ), glioma ( 34 ), and melanoma ( 35 ). In our previous study, we found that NCRNA00173 also contributes to the chemoresistance of colorectal cancer ( 19 ) and SCLC by acting as competing endogenous RNA ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a novel epigenetic mechanism of IRS-4 upregulation has been described in melanoma [ 17 ]. The upregulation occurs via an increase of endogenous long intergenic non-protein-coding RNA-173, a natural sponge of microRNA-493 (miR-493), which in turn induces IRS-4 transcript degradation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%